2012
DOI: 10.1371/journal.pone.0037599
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Intraneuronal Elevation of αII-Spectrin Breakdown Product SBDP120 in Rodent Forebrain Accelerates in 3×Tg-AD Mice

Abstract: Spectrins line the intracellular surface of plasmalemma and play a critical role in supporting cytoskeletal stability and flexibility. Spectrins can be proteolytically degraded by calpains and caspases, yielding breakdown products (SBDPs) of various molecular sizes, with SBDP120 being largely derived from caspase-3 cleavage. SBDPs are putative biomarkers for traumatic brain injury. The levels of SBDPs also elevate in the brain during aging and perhaps in Alzheimer’s disease (AD), although the cellular basis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Spectrins were identified as one of the proteins deposited in Aβ plaques [ 54 , 55 ]. α-spectrin was shown to be cleaved by calpain and caspase-3 and its 120-kDa breakdown product was increased in the aged brains from both AD patients and 3×TgAD mice [ 56 - 59 ], and is therefore considered as a potential AD biomarker [ 60 ]. Recently, β-spectrin was also found to be cleaved by calpain and caspase under neurotoxic and traumatic brain-injury conditions [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Spectrins were identified as one of the proteins deposited in Aβ plaques [ 54 , 55 ]. α-spectrin was shown to be cleaved by calpain and caspase-3 and its 120-kDa breakdown product was increased in the aged brains from both AD patients and 3×TgAD mice [ 56 - 59 ], and is therefore considered as a potential AD biomarker [ 60 ]. Recently, β-spectrin was also found to be cleaved by calpain and caspase under neurotoxic and traumatic brain-injury conditions [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that a progressive increase in α‐II spectrin proteolysis (Cai et al . ; Hwang et al . ), a calcium‐dependent process linked to Purkinje cell toxicity (Mansouri et al .…”
Section: Introductionmentioning
confidence: 99%
“…[ 127 128 ] In addition, caspase-3 activity is associated with proteolytic degradation of cytoskeletal proteins, such as αII-spectrin, further contributing to neuronal pathology in human TBI and animals models,[ 129 130 ] and preclinical evidence suggests that this pathology might be exacerbated by the presence of existing neurodegenerative disease. [ 131 ]…”
Section: Role Of Caspase-mediated Apoptosis In Neurodegenerative Disomentioning
confidence: 99%
“…[ 130 ] Interestingly, increased levels of SBDP120 after experimental TBI were observed in the triple transgenic AD mice (3xTg-AD) compared to wild-type controls of the same background. [ 131 ] Clinical studies in severe TBI have confirmed utility of SBDP120 as a sensitive biomarker of caspase-3 activation exclusively associated with apoptotic cell death. [ 129 ] Other studies have confirmed the utility of SBDP145 and SBDP150 as highly useful biomarkers of calpain activation primarily associated with necrosis.…”
Section: Caspase-cleaved Products As Biomarkers Of Brain Apoptosis Fomentioning
confidence: 99%
See 1 more Smart Citation